The influence of the COVID-19 pandemic on appendicitis in children: the experience of a public hospital in Brazil - Almeida, Renê Mariano de; Roberto Paulo Correia, Araujo (Revista de Ciências Médicas e Biológicas, 2024)
In the SARS-CoV-2 pandemic, children and adults with non-COVID-19 emergencies, such as acute appendicitis (AA), requiring surgical treatment, may have had longer disease evolution times with possible repercussions on the results and use of open appendectomies. Objective: To compare the evolution and severity of AA in children and the results of laparoscopic and open appendectomies in the trans-pandemic period with the pre-pandemic period. Methodology: Retrospective study evaluating two series of children who underwent appendectomy at a public reference hospital, between March 2019 and February 2020 (pre-pandemic) and the same period from 2020 to 2021 (trans-pandemic). The analysis included the time of symptom progression, severity, types of appendectomy, and outcomes. Results: In these 2 years, 249 appendectomies were performed in children under 15: 131 in the pre-pandemic period and 118 in the trans-pandemic period. 218 (87.5%) procedures were by laparotomy and 31 (12.5%) procedures were laparoscopically. The duration of symptoms was 3.2±2.9 days in the pre-pandemic period and 3.3±2.8 days in the trans-pandemic period, and there was a lower number of children admitted within 24 hours (20.3%) of the onset of symptoms before the pandemic (vs. 34.1%). Complication rates were 32.9% with laparotomy and 12.9% with laparoscopy. Reoperations were more frequent in the pandemic than in the pre-pandemic period (11.0% vs. 4.6%) and the hospital stay was longer (5.6±4.3 vs. 4.7±2.9 days). Conclusion – During the pandemic, children with AA took longer to have access to surgical treatment and had more complications, reoperations, and longer hospitalization time, especially with open appendectomy.